How much Blood Transfusion Protocols Are Followed among Health Care Providers in the Tertiary Care Hospitals of Rawalpindi and Islamabad (Medical Forum Monthly, 2024)
Objective: The high-ceilinged importance given to safe blood transfusion, a study was conducted in the teaching hospitals of Islamabad and Rawalpindi to ascertain how much blood transfusion protocols are followed.Study Design: Cross sectional study.Place and Duration of Study: This study was carried out in the Teaching Hospitals of Islamabad and Rawalpindi, between Oct, 2007 to Dec, 2007Materials and Methods:, A total of seventy six health care professionals from surgical and allied specialties were put forward a questionnaire Performa relating to as to whether departmental guidelines for blood transfusion are followed or not.Results: Out of total studied sample i.e. seventy six in total, forty health care personals i.e. 52.63% affirmed that they do follow departmental guidelines for blood transfusion, whereas thirty six personals i.e. 47.37% were lacking the follow-up of standard protocols in their settings.Conclusion: In the study 47.37% i.e. thirty six in number of considered health care professionals were of the opinion that they do not pursue in spirit departmental guidelines regarding blood and blood product transfusion.